LINGUISTIC FEATURES OF AVIATION TERMINOLOGY IN UZBEK AND ENGLISH LANGUAGES - Xilola Jo'raboyeva (Journal of new century innovations, 2023)
Abstract: The article discusses the features of aviation terminology in English, and also describes the difficulties that a translator faces when translating technical literature. The analysis of terms is based on examples from the Dictionary of International Civil Aviation.